Automated Tele-monitoring System - Rama, Kovur (Techniques and Innovation in Engineering Research Vol. 3, 2022)
A lot of technological shifts are observed in every walk of life in this world. Especially, in telemedicine. The most important challenge is to bring the patient on time to the hospital by clearing the traffic. In the present investigation, a Zigbee-based traffic clearance system is designed with both transmitter and receiver sections. The transmitter section located in the emergency vehicle, has four key switches. The receiver section uses light emitting diodes (LED) to display red, orange, and green lights. When both Zigbee’s are in range and if the driver presses a button on the keypad, indicating the direction in which the ambulance is arriving, the green light glows in that direction, while in all the other directions, the red light glows. In this way, the patient is taken on time to the hospital.